AUTHORSHIP, QUALITY AND PRICE AS FACTORS INFLUENCING UTILISATION OF TEXTBOOKS IN PRIMARY SCHOOLS IN OYO STATE, NIGERIA (2012)
Textbooks play central role in teaching and learning in schools, particularly, in primary schools. Difficult and poorly written textbooks in the early grades contribute to the high drop-out rate of pupils in Nigeria. Utilisation of textbooks may be influenced by several factors, especially authorship, quality and price. However, there is a dearth of information on how the factors relatively and jointly influence utilisation of textbooks in primary schools in Nigeria. The study, therefore investigated the influence of authorship, quality and price on textbook utilisation in primary schools in Oyo State. The ex-post facto type of descriptive survey research design was used. Multi-stage sampling technique was adopted to select 7 out of the 8 educational zones in Oyo State. Eight schools each were selected from the 7 zones. Fifty-six head teachers, 130 teachers, one arm (intact class) of primary five pupils (1,680) and parents/guardians (1,680) were randomly selected in the schools. Furthermore, four sessions of Key Informant Interview (KII) were conducted with authors, publishers, Officials of the Ministry of Education and State Universal Basic Education Board. Three instruments were used: Teachers' Textbook Assessment Scale (r=0.95); Parents' Textbook Assessment Scale (r=0.95), and Pupils' Textbook Assessment Scale (r=0.77). Data were analysed using descriptive statistics, Pearson Product Moment Correlation and multiple regression. Content analysis was used for the qualitative data. Daily percentage usages of textbooks by the pupils were: mathematics (83.2%), English Language (74.4%), basic science (38.1%) and social studies (33.9%). Authorship, quality and price had significant influence on utilisation of textbooks (F= (10, 19), 4.858 p<0.05) and contributed 85% to the variance of the independent variable. The relative contributions were as follows: authorship, (? -.546; t=-2.621), quality (?= -.421; t=-2.183), price (? =.282; t=1.171). Also, significant relationship existed between quality and utilisation of textbooks: (r=0.72) for mathematics textbooks; (r=0.67) for English Language textbooks; (r = 0.66) for science textbooks and (r=0.40) for social studies textbooks. Significant relationship existed only between authorship and utilisation of English Language textbooks (r=0.83) while none existed for others. There were significant differences in quality and price of mathematics, English Language and social studies textbooks by different publishers. The average prices of textbooks across publishers as at the time of this study were as follows:( N660) for mathematics, (N555) for English Language, (N537) for science and (N457) for social studies. The authors were highly qualified as majority (69.0%) of them were Ph.D. holders who wrote in their areas of specialisations. This reflected in the high quality textbook produced. The KII revealed that all the publishers indicated their authors qualifications and experience as important criteria for selection. More than half of the authors (78.6%) were male. Approximately, 60% of the production cost was on paper procurement. Authorship, quality and price influenced utilisation of textbooks in Oyo State. Therefore, government should ensure evaluation in respect to authorship and quality of textbooks by experts before they are adopted for schools in Oyo State. The government should also reduce taxes on raw materials that publishers use in textbook production.